Regulatory T-Cell Impairment in Cystic Fibrosis Patients with Chronic Pseudomonas Infection - Hector, Andreas; Schäfer, Heike; Pöschel, Simone; Fischer, Alexandra; Fritzsching, Benedikt; Ralhan, Anjali; Carevic, Melanie; Öz, Hasan; Zundel, Sabine; Hogardt, Michael; Bakele, Martina; Rieber, Nikolaus; et al. (American journal of respiratory and critical care medicine, 2015)
Rationale: Patients with cystic fibrosis (CF) lung disease have chronic airway inflammation driven by disrupted balance of T-cell (Th17 and Th2) responses. Regulatory T cells (Tregs) dampen T-cell activation, but their role in CF is incompletely understood.Objectives: To characterize numbers, function, and clinical impact of Tregs in CF lung disease.Methods: Tregs were quantified in peripheral blood and airway samples from patients with CF and from lung disease control patients without CF and healthy control subjects. The role of Pseudomonas aeruginosa and CF transmembrane conductance regulator (CFTR) in Treg regulation was analyzed by using in vitro and murine in vivo models.Measurements and Main Results: Tregs were decreased in peripheral blood and airways of patients with CF compared with healthy controls or lung disease patients without CF and correlated positively with lung function parameters. Patients with CF with chronic P. aeruginosa infection had lower Tregs compared with patients with CF without P. aeruginosa infection. Genetic knockout, pharmacological inhibition, and P. aeruginosa infection studies showed that both P. aeruginosa and CFTR contributed to Treg dysregulation in CF. Functionally, Tregs from patients with CF or from Cftr−/− mice were impaired in suppressing conventional T cells, an effect that was enhanced by P. aeruginosa infection. The loss of Tregs in CF affected memory, but not naive Tregs, and manifested gradually with disease progression.Conclusions: Patients with CF who have chronic P. aeruginosa infection show an age-dependent, quantitative, and qualitative impairment of Tregs. Modulation of Tregs represents a novel strategy to rebalance T-cell responses, dampen inflammation, and ultimately improve outcomes for patients with infective CF lung disease.